Exploring the Impact of Brand Equity, Corporate Reputation, and Product Quality on Customer Loyalty toward a National Newspaper in Surabaya - Merlin Cecilia (iBuss Management, 2014)
National and local newspaper competes for gaining more market share. It is also happened with XYZ newspaper. XYZ newspaper  as the biggest national newspaper in Indonesia tends to have low market share in other area outside Jakarta, especially in Surabaya.  Previous researches showed that brand equity, corporate reputation, and product quality are able to influence customer loyalty which can lead to increasing number ofcustomer and market share. Therefore, this research is conducted to examine the influence of brand equity, corporate reputation, and product quality on customer loyalty toward XYZ newspaper in Surabaya. Quantitative method is used and multiple regression is chosen as the analytical method. With 95 samples collected through simple random sampling method, the result of the research shows that brand equity, corporate reputation, and product quality simultaneously have significant influence on customer loyalty toward XYZ newspaper in Surabaya. Also, corporate reputation and product quality individually have significant influence on customer loyalty toward  XYZ newspaper  in Surabaya. But, brand equity as individual has no significant influence on customer loyalty toward  XYZ newspaper  in Surabaya. Based on this fact, author concludes that  XYZ newspaper  should focus on improving corporate reputation and product quality, while also enhances its brand equity in order to increase the customer loyalty.  Keywords: Brand Equity, Corporate Reputation, Product Quality, Customer Loyalty, Newspaper